A new subspecies of Araragi panda Hsu & Chou (Lepidoptera, Lycaenidae, Theclini) from Sichuan, western China - Hsu, Yu-Feng; Li, Ai-Min (Zootaxa, 2019)
Araragi panda sichuanensis Hsu & Li, subsp. nov. (Theclinae: Theclini) is described from Baoxing, Sichuan Province of western China, the type locality of the Giant Panda Ailuropoda melanoleuca. The present article also clarifies the identity of the hostplant for A. panda previously mis-identified. It should be the wheel wingnut (Cyclocarya paliurus) instead of the iron walnut (Juglans sigllata) recorded in literature. C. paliurus is sometimes called “the Giant Panda in plant kingdom” in China.